2016
DOI: 10.14309/crj.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

The Black Esophagus: A Rare But Deadly Disease

Abstract: We present a series of cases of acute esophageal necrosis along with a video demonstration. The video captures a case showing the severity of necrosis of the esophageal mucosa; an orogastric tube easily passed through the esophageal lumen and into the right hemithorax. The series also demonstrates the severity of this illness, with an associated high mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…A review of the literature found that 19 of 163 patients with AEN progressed to esophageal stricture 3 weeks to 2 months after the onset of AEN [3, 613]. Gurvits et al reported that coronary artery disease, recent surgery, and gastroduodenal pathology may be associated with esophageal stricture [1].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature found that 19 of 163 patients with AEN progressed to esophageal stricture 3 weeks to 2 months after the onset of AEN [3, 613]. Gurvits et al reported that coronary artery disease, recent surgery, and gastroduodenal pathology may be associated with esophageal stricture [1].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that timely patient stabilization and fluid resuscitation play pivotal roles in properly managing these difficult patients [6]. Furthermore, as seen from other published cases on the topic, acid suppression with high dose intravenous proton pump inhibitors, nil-peros (NPO) restriction, and glycemic control should immediately be initiated [7]. However, with regard to adequate nutrition for patients, the management tends to be up to the discretion of the clinical provider.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports published in literature reviews were also included on the condition that patient history was sufficiently detailed. The endoscopy series initially included 88 publications, of which 26 publications on a total of 41 deceased patients were retained (Gurvits et al 2015;Ben Soussan et al 2002;Averbukh et al 2018;Barnes et al 2014;Day and Sayegh 2010;Del Hierro 2011;Essamri et al 2001;Grudell et al 2006;Julian Gomez et al 2008;Kalva et al 2016;Katsinelos et al 2004;Koop et al 2016;Lahbabi et al 2013;Maher and Nassar 2008;Odelowo et al 2002;Ramos et al 2008;Rodrigues et al 2016;Roman Fernandez et al 2014;Salem et al 2015;Shafa et al 2016;Shah et al 2017;Sharma et al 2016;Singh et al 2011;Wu and Wu 2014;Monteiro et al 2019;Khan et al 2019). The autopsy series initially comprised 13 publications, of which 11 publications on a total of 17 patients were retained in this review.…”
Section: Literature Review Methodsmentioning
confidence: 99%